In vitro performance of Lifetech IBS Angel™ (iron-based bioresorbable scaffold) stents during overdilation for use in pediatric patients - Bjorkman, Kurt; Maldonado, Jennifer R.; Saey, Stephanie; McLennan, Daniel (Frontiers in Cardiovascular Medicine, 2022)
Objectives The objective of this study was to assess the mechanical performance of the Lifetech IBS Angel stents during overdilation as is often required in pediatric applications; including time of first fracture, foreshortening, and the type of fracturing that occurs. Materials and methods In vitro testing was performed and repeated for each stent three times under physiologic conditions with continuous audiovisual imaging allowing for post-testing evaluations. Assessment of sheath fit was also completed. Results A total of 47 stents on monorail system were overdilated to complete fracture after passing through either a 4 or 5 French sheath. First strut fracture occurred in 4 and 6 mm stents when they reached greater than 50% overexpansion. Larger stents could achieve at least 30% increased diameter prior to first strut fracture. No fragmentation of any of the stents was seen throughout testing. Conclusion The IBS Angel has thin struts allowing for a lower profile with increased maneuverability and use with smaller sheaths. Embolization potential of strut fragments was not seen. Increased diameter well beyond design parameters was seen in all with acceptable foreshortening.